Modern Methods of Linguopoetic Analysis in Uzbek Children's Poetry and their Educational Significance - Sobirova Dilafruz Abdulkhay kizi (Scientific Trends, 2025)
This article discusses the theoretical and practical foundations of linguopoetic analysis of the language of Uzbek children’s poetry. The study highlights the importance of linguopoetic analysis in revealing the aesthetic, emotional, and figurative capacities of language and examines modern interactive methods of teaching it. Practical examples illustrate how techniques such as “Brainstorming,” “Blitz Survey,” “Mind-map,” role-playing, and creative tasks contribute to the development of students’ speech competence, the formation of aesthetic taste, and the expansion of creative thinking.
Keywords: Uzbek children’s poetry, linguopoetics, educational significance, interactive methods, creative thinking, speech competence, aesthetic taste, multimedia, methodology.